Contextualization of Early Marriage Hadith: Analysis of Marriage Hadith ‘Aisha with Sociology Approach - Amelia Damayanti; Siti Zuhrotun Ni’mah (International Journal of Research, 2023)
The current reality is that many parties interpret hadith only textually without understanding the sociological meaning related to the conditions at that time. Likewise regarding the hadith regarding Aisyah's marriage which is often packaged to legalize child marriage at this time. So the presence of this research provides a more comprehensive insight into this issue. The research method used in this research is a literature review with primary data in the form of hadith books and history regarding sociological facts and the history of hadith regarding Aisyah's marriage. The results of this research indicate that interpreting the hadith of 'Aisyah's marriage needs to be studied sociologically both in terms of sanad and matan. So in the current context, child marriage cannot be carried out because it can have a negative impact on physical, mental, social and economic health conditions.